Investigating Adaptive ASEAN Cultural Diversity Through Users’ Mental Models for User Interface Design. - Aslina Baharum; Azizah Jaafar (2014)
Nowadays, the Web has become the main gateway for organisations as well as making information accessible through the World Wide Web. Previous usability studies have focused on the development and user-centered design of websites. The location of objects through the use of a mental model is able to help users to navigate the Web and access information easily. The rationale for developing a mental model through an experimental study is to protect the high investment necessary for Web development through adaptive cultural diversity. The specific environment of a different country can inter-operate in the context of adaptation and needs to account for adaptive support in the context of collaborative activities. This study investigates cultural adaptivity with respect to ASEAN countries by identifying a mental model through the location of Web objects via a website user interface. Almost half of the located Web objects are found to be consistent with previous studies that examined user expectations regarding the location of general websites, e-commerce websites and library websites. There were, however, diversities among the studies involving the location of various Web objects. In this study, another three Web object elements are included, namely, "Language", "Content" and "Calendar". It is of interest to note that the participants from all the geographical locations in the ASEAN countries included in this study had similar expectations for certain Web objects. It is therefore possible that the influence of multinational websites and cross-regional Web browsing has significantly shaped the website layout expectations of typical Web users.